DESIGN OF MOORING SYSTEM ON FLOATING TIDAL CURRENT TURBINE AS THE BASIS FOR DEVELOPMENT OF TURBINE FARM IN LARANTUKA STRAIT - Duanita Hermilia - NIM: 15514005, Rizky
one of invention in marine energy field is the design of floating tidal current. In a boundary area of strait, turbine farm should be considered in order to prevent accident between turbines or disturbing turbine’s movement while operating. This final year project will discuss about design and analysis of mooring system on floating tidal current by reguler wave. Analysis will be performed by Orcaflex and MOSES in 2 conditions, intact and damage. This analysis is purpose to get structure respons due to environment load. The respons are structure’s offset, mooring rope’s offset, and maximum tension according to criterion from API RP2SK. From that result, the safety distance between one turbine to others can be concluded. With the planned location in strait, and the analysis result of displacement turbine, then it can be known the number of turbines that can be built to maximize the strait which provided to turbine farm development.